Disruption of the Global Supply Chain as a Result of the COVID-19 Pandemic, and the Response of Supply Chain Companies - Phuong, Pham Thu (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2022)
The COVID-19 pandemic has caused one of the most extensive disruptions in the last decades which has seen the breaking of many global supply chains. The pandemic changed the world, requiring governments, businesses, and individuals to adapt to new situations and take immediate actions to sustain. Based on the evaluation of the disruptions of global supply chains due to the COVID -19 pandemic, the article focuses on the implementation of appropriate strategies of multinational companies and suppliers to overcome the disruptions of the supply chains and to improve their international production resilience.